Extension of cervical screening intervals with primary human papillomavirus testing: observational study of English screening pilot data. (31st May 2022) - Rebolj, Matejka; Cuschieri, Kate; Mathews, Christopher S; Pesola, Francesca; Denton, Karin; Kitchener, Henry
Abstract: Objectives: To provide updated evidence about the risk of cervical intraepithelial neoplasia grade 3 or higher (CIN3+) and cervical cancer after a negative human papillomavirus (HPV) test in primary cervical screening, by age group and test assay. Design: Observational study. Setting: Real world data from the English HPV screening pilot's first and second rounds (2013-16, follow-up to end of 2019). Participants: 1 341 584 women. Interventions: Cervical screening with HPV testing or liquid based cytological testing (cytology or smear tests). Women screened with cytology were referred to colposcopy after high grade cytological abnormalities or after borderline or low grade abnormalities combined with a positive HPV triage test. Women screened with HPV testing who were positive were referred at baseline if their cytology triage test showed at least borderline abnormalities or after a retest (early recall) at 12 and 24 months if they had persistent abnormalities. Main outcome measures: Detection of CIN3+ and cervical cancer after a negative HPV test. Results: For women younger than 50 years, second round detection of CIN3+ in this study was significantly lower after a negative HPV screen in the first round than after cytology testing (1.21/1000 v 4.52/1000 women screened, adjusted odds ratio 0.26, 95% confidence interval 0.23 to 0.30), as was the risk of interval cervical cancer (1.31/100 000 v 2.90/100 000 woman years, adjusted hazard ratio 0.44, 0.23 to 0.84). Risk of an incident CIN3+ detected at the second screening round in the pilot five years after a negative HPV test was even lower in women older than 50 years, than in three years in women younger than 50 years (0.57/1000 v 1.21/1000 women screened, adjusted odds ratio 0.46, 0.27 to 0.79). Women with negative HPV tests at early recall after a positive HPV screening test without cytological abnormalities had a higher detection rate of CIN3+ at the second routine recall than women who initially tested HPV negative (5.39/1000 v 1.21/1000 women screened, adjusted odds ratio 3.27, 95% confidence interval 2.21 to 4.84). Detection after a negative result on a clinically validated APTIMA mRNA HPV test was similar to that after clinically validated cobas and RealTime DNA tests (for CIN3+ at the second round 1.32/1000 v 1.14/1000 women screened, adjusted odds ratio 1.05, 0.73 to 1.50). Conclusions: These data support an extension of the screening intervals, regardless of the test assay used: to five years after a negative HPV test in women aged 25-49 years, and even longer for women aged 50 years and older. The screening interval for HPV positive women who have negative HPV tests at early recall should be kept at three years.